2018
DOI: 10.3390/bs8080068
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variations of Fertility Control Behavior among Rural Reproductive Women in Bangladesh: A Hierarchical Analysis

Abstract: Women’s fertility decision is quite difficult in male-dominant rural culture due to their poor reproductive autonomy. A cross-sectional survey was conducted in rural community of Bangladesh between November 2017 and February 2018 among 1285 respondents selected by multi-stage stratified sampling to explore regional variations of rural women’s fertility control behavior and its determinants using hierarchical and other inferential statistics. Data collection was done by face-to-face interview using questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The low CPR of Muslim women confirms the presence of the preference for sons. These findings are similar to the findings of other studies that took place in Bangladesh (Hoq, 2019;Visaria, 2015;Alam et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The low CPR of Muslim women confirms the presence of the preference for sons. These findings are similar to the findings of other studies that took place in Bangladesh (Hoq, 2019;Visaria, 2015;Alam et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…This is analogous to the studied cases in Bangladesh. 25 The magnitude of women's empowerment in regulating fruitfulness was also alluded to in a prior study conducted in Bangladesh. 26 The current research hints that access to media has an important and positive influence on reducing fertility rates among women.…”
Section: Discussionmentioning
confidence: 99%
“…We also found the divisional variations of modern contraception use, with modern contraception was found to be lower in the Sylhet, Chattogram and Barishal divisions and higher in the Rangpur, Mymensingh and part of the Rajshahi division. Previous studies in Bangladesh also reported a higher odd of modern contraception non-use in the Sylhet, Barishal and Chattogram divisions and lower odds of non-modern contraception in the Rangpur, Mymensingh and Rajshahi divisions [18, 27]. However, our findings were based on cluster level (smallest area under division) estimates which enable us to identify specific areas of contraception unmet need.…”
Section: Discussionmentioning
confidence: 45%
“…Chattogram divisions and lower odds of non-modern contraception in the Rangpur, Mymensingh and Rajshahi divisions [18,27]. However, our findings were based on cluster level (smallest area under division) estimates which enable us to identify specific areas of contraception unmet need.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation